Not(ch) Your Average Tax System : Corporate Taxation under Weak Enforcement - Bachas, Pierre (World Bank, Washington, DC, 2018)
How should developing countries tax corporate income? This paper studies this question in Costa Rica, where firms face discontinuously higher average tax rates on profits when their revenue marginally increases. The paper combines a discontinuity and a bunching design to estimate the profit elasticity and separate it into revenue and cost elasticities. Faced with higher tax rates, firms slightly reduce revenue but considerably increase costs, generating a large elasticity of profits. In this context, the revenue maximizing rate for profit taxation is below 25 percent and broadening the tax base while lowering the rate can increase revenue for these firms by 80 percent.